High performance enzymatic synthesis of oleyl oleate using immobilised lipase from Candida antartica - Salina Mat Radzi; Mahiran Basri; Abu Bakar Salleh; Arbakariya Ariff; Rosfarizan Mohammad; Mohd. Basyaruddin Abdul Rahman; Raja Noor Zaliha Raja Abdul Rahman (Universidad Católica de Valparaíso, 2005)
High performance enzymatic synthesis of oleyl oleate, a liquid wax ester was carried out by lipase-catalysed esterification of oleic acid and oleyl alcohol. Various reaction parameters were optimised to obtain high yield of oleyl oleate. The optimum condition to produce oleyl oleate was reaction time; 5 min, organic solvents of log P ≥ 3.5, temperature; 40-50°C, amount of enzyme; 0.2-0.4 g and molar ratio of oleyl alcohol to oleic acid; 2:1. The operational stability of enzyme was maintained at >90% yield up to 9 cycles. Analysis of the yield of the product showed that at optimum conditions, >95% liquid wax esters were produced.